Adverse Childhood Experiences, Domestic Violence and Substance Misuse: An Action Research Study on Routine Enquiry and Practice Responses - Morton, Sarah; Curran, Megan; Barry O'Gorman, Mary (Frontiers in Psychiatry, 2022)
The long-term impacts of Adverse Childhood Experiences (ACEs) are of increasing interest to researchers and practitioners, including the effectiveness of screening for ACEs to improve health and social outcomes. Despite a focus on implementing such practices, there has been little focus on ACEs experiences for women experiencing domestic violence and substance use, or consideration of practice responses around ACEs routine enquiry for domestic violence and related services. The Irish study discussed in this paper used an action research approach to implement ACEs routine enquiry within a domestic violence service for women accessing the service (n=60), while also utilising co-operative inquiry groups for practitioners both within the organisation (n=10) and with those working in associated fields of infant mental health, child protection, substance misuse and welfare and community support (n=7). Of the 60 women who completed the ACEs routine enquiry in the study, over one-half (58 per cent) reported experiencing at least two ACEs in their childhood, including one-third of all respondents reporting experiencing four or more; service users reported significant levels of overlap between direct child maltreatment and adverse home environments. Reported parental substance misuse with the home environment was substantially higher than in general population studies. These findings offered early indications of both ACEs prevalence as well the types of ACEs that most define the experiences of the women presenting to a domestic violence service that supports women with substance misuse and other related issues. This paper discusses the ways in which the co-operative inquiry groups used this information and other processes to enhance practitioner, organisational, and inter-agency understanding and service responses. The practitioners felt that this form of ACEs routine enquiry, while not an end in itself, was a useful tool to engage women in conversations about trauma and intergenerational patterns and a basis for developing trauma-informed interventions. We conclude with discussion about: considerations of the risks of ‘individualising’ women’s traumatic experiences; skills and supports for practitioners; and resource implications. .